A Case-Control Study of Risk Factors for Type 2 Diabetes Mellitus in Vietnam - Nguyen, Thanh Chung (Curtin University, 2016)
A case-control study including 599 type 2 diabetes (T2D) cases and 599 controls was conducted in Northern Vietnam between 2013 and 2015 to investigate the associations between dietary, lifestyle factors and T2D risk. High consumption of green tea, coffee, and moderate intensity of activity were inversely associated with reduced odds of T2D. The present study found that there are inverse associations between habitual tea, coffee consumption, physical activity and risk of T2D among Vietnamese adults.